2015
DOI: 10.1038/srep16209
|View full text |Cite
|
Sign up to set email alerts
|

Eryptosis Indices as a Novel Predictive Parameter for Biocompatibility of Fe3O4 Magnetic Nanoparticles on Erythrocytes

Abstract: Fe3O4 magnetic nanoparticles (Fe3O4-MNPs) have been widely used in clinical diagnosis. Hemocompatibility of the nanoparticles is usually evaluated by hemolysis. However, hemolysis assessment does not measure the dysfunctional erythrocytes with pathological changes on the unbroken cellular membrane. The aim of this study is to evaluate the use of suicidal death of erythrocytes (i.e. eryptosis indices) as a novel predictive and prognostic parameter, and to determine the impact of Fe3O4-MNPs on cellular membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
57
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(63 citation statements)
references
References 60 publications
2
57
1
3
Order By: Relevance
“…It is, however, possible that DEHP has a non-specific effect with regard to lipid flip-flop and that other lipids also have increased transverse movement after RBCs are exposed to DEHP. The effect in which stomatocyte formation is seen simultaneously with appearance of exposed PS, has been seen elsewhere, with the addition of nanoparticles to RBCs [42]; small molecules have also been shown previously to be able to cause lipid flip-flop between leaflets [43,44]. …”
Section: Discussionmentioning
confidence: 99%
“…It is, however, possible that DEHP has a non-specific effect with regard to lipid flip-flop and that other lipids also have increased transverse movement after RBCs are exposed to DEHP. The effect in which stomatocyte formation is seen simultaneously with appearance of exposed PS, has been seen elsewhere, with the addition of nanoparticles to RBCs [42]; small molecules have also been shown previously to be able to cause lipid flip-flop between leaflets [43,44]. …”
Section: Discussionmentioning
confidence: 99%
“…16 Nemmar et al found that ultra-small super paramagnetic iron oxide nanoparticles (magnetite, Fe 3 O 4 , 4-6 nm) caused thrombosis and cardiac oxidative stress and DNA damage in mice following acute intravenous administration. 17 Li's group 18 reported that Fe 3 O 4 magnetic nanoparticles (72.6 AE 0.57 nm) cause eryptosis, and changes in ow properties of blood. Moreover, some researchers evaluated the haematotoxicity of magnetic nanoparticles coated with dimercaptosuccinic acid (DMSA) and polyethylene glycol (PEG) in vitro and in vivo in a rat model.…”
Section: Introductionmentioning
confidence: 99%
“…Free radicals are shown to increase eryptosis . Silver nanoparticles can have adverse effects on cells given the large surface area and possibility of ROS creation and hence causing oxidative stress; eryptosis triggered by Fe 3 O 4 magnetic nanoparticles and by silver ions have been recently discussed. Increased oxidative stress and higher level of eryptosis are observed in diabetic conditions .…”
Section: Introductionmentioning
confidence: 99%